Aerodynamic analysis and experiment of a micro flapping wing rotor - Li, Hao (Cranfield University, 2015)
This project is aimed at developing a bio-inspired flyable micro/nano aerial vehicle (MAV) of high agility and performance capable of vertical take-off and landing and hovering (VTOLH). To achieve the aim, a novel flapping wing rotor (FWR) concept invented by Dr. Guo has been adopted, which is ideal for MAVs of sub 60 gm and especially for nano scale of sub 5 gm according to aerospace industry’s definition. The advantages and potential of the FWR concept for MAV development has been studied consistently by Dr. Guo’s research team in the last five years. However making a flyable micro FWR model especially in sub 5gm and demonstrate its VTOLH feasibility remains as a big challenge and has not been achieved in previous projects. To meet the above objective, the first achievement in the project is the successful design, build and test of a flyable micro FWR model (FWR-EX1) of only 3 gm based on off-the-shelf available micro motor. The key breakthrough is to achieve the necessary large aeroelastic twist of the flapping wing during the upstroke in an adaptive manner for structural and aerodynamic efficiency. To achieve the next objective for design and performance improvement, study has also been focused on deeper scientific understanding and analysis of the FWR mechanisms. Attention has therefore been paid to a systematic study on aerodynamic modelling and efficiency of the FWR. The method is based on a revised quasi-steady aerodynamic model that combines the theoretical method and experimental data. The numerical results of the revised quasi-steady aerodynamic model are in agreement with existing results obtained via CFD methods. Based on the model and analysis, the optimal kinematics for the FWR has been determined. Subsequently a comparison of the FWR aerodynamic efficiency was made with two other most studied configurations of MAVs, the insect flapping wing and rotorcraft ... [cont.].
Keywords: Flapping Wing Rotor; MAV; VTOLH; quasi-steady aerodynamics; efficiency